Pro Vue.js 2 - Freeman, Adam (Apress, 2018)
Explore Vue.js to take advantage of the capabilities of modern browsers and devices using the fastest-growing framework for building dynamic JavaScript applications. You will work with the power of the Model-View-Controller (MVC) pattern on the client, creating a strong foundation for complex and rich web apps. Best-selling author Adam Freeman explains how to get the most from Vue.js 2. He begins by describing the MVC pattern and the benefits it can offer, and then shows you how to use Vue.js in your projects, starting from the nuts-and-bolts and building up to the most advanced and sophisticated features, going in-depth to give you the knowledge you need. Chapters include common problems and how to avoid them. What You'll Learn: Gain a solid architectural understanding of the MVC pattern Create rich and dynamic web app clients using Vue.js 2 Extend and customize Vue.js Test your Vue.js projects.